2021
DOI: 10.4254/wjh.v13.i12.1956
|View full text |Cite
|
Sign up to set email alerts
|

Liver manifestations and complications in inflammatory bowel disease: A review

Abstract: Hepatobiliary manifestations are common in inflammatory bowel disease (IBD), with 30% of patients presenting abnormal liver tests and 5% developing chronic liver disease. They range from asymptomatic elevated liver tests to life-threatening disease and usually follow an independent course from IBD. The pathogenesis of liver manifestations or complications and IBD can be closely related by sharing a common auto-immune background (in primary sclerosing cholangitis, IgG4-related cholangitis, and autoimmune hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 81 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Firstly, we applied SL for the first time to alleviate DSS induced colitis in mice, providing a new idea for the treatment of colitis. Secondly, considering that 30% of IBD patients exhibit abnormal liver examinations, 2 we also reported the anti-inflammatory regulatory effects of SL on the liver. Thirdly, we found that intervention with SL displayed a more effective therapeutic effect compared to the use of LA alone, with HS showing the most significant effect.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Firstly, we applied SL for the first time to alleviate DSS induced colitis in mice, providing a new idea for the treatment of colitis. Secondly, considering that 30% of IBD patients exhibit abnormal liver examinations, 2 we also reported the anti-inflammatory regulatory effects of SL on the liver. Thirdly, we found that intervention with SL displayed a more effective therapeutic effect compared to the use of LA alone, with HS showing the most significant effect.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, IBD is not confined solely to the gastrointestinal tract, often triggering inflammatory responses that extend to other areas of the body, particularly leading to complications related to liver inflammation or damage. 2,3 Furthermore, the global prevalence of IBD is on the rise, affecting millions of people and imposing substantial societal and economic burdens on the government and healthcare system. 4 While the exact etiology of IBD is not yet clear, it is widely hypothesized to stem from intricate interactions between the host and the gut microbiota, such as the composition of the intestinal microbiota, aberrant immune responses, and compromised intestinal mucosal barriers.…”
Section: Introductionmentioning
confidence: 99%
“…MTX is commonly used for the induction or maintenance of disease remission and is often associated with alterations in liver enzymes (up to 15–50% of patients) [ 85 ]. However, rather than causing NAFLD, it exerts its hepatotoxic effect mainly by inducing liver fibrosis (with an estimated risk of 5%), especially in the context of long-term and high-dose use [ 86 ], even if this risk seems also to be overestimated according to recent evidence [ 87 ]. Indeed, a multicenter longitudinal British cohort study investigated the impact of long-term MTX therapy on liver fibrosis.…”
Section: Pathogenetic Mechanisms Of Nafld In Ibdmentioning
confidence: 99%
“…Clinically, IBD overlaps with hepatobiliary conditions, as 30% IBD cases have abnormal liver tests and around 5% of them develop chronic hepatobiliary disease 7, 8 . The first responders to extraneous dangers due to leakiness of the gut during colitis are the Kupffer cells, which keep a check on the content flowing through the portal system 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, IBD overlaps with hepatobiliary conditions, it has been reported that 30% of IBD cases have abnormal liver function tests and around 5% of them even develop chronic hepatobiliary diseases 7, 8 . During colitis, the first responders to extraneous agents incoming from the leaky gut are the Kupffer cells 9 .…”
Section: Introductionmentioning
confidence: 99%